Sexual dysfunctions in female university students and the correlation with body image: a cross-sectional study - Paula Rodrigues Eberhardt; Valentina Lucia La Rosa; Taís Marques Cerentini; Salvatore Caruso; Rosalia Ragusa; Pasquale De Franciscis; Gaetano Riemma; Cislaine Machado de Souza; Luis Henrique Telles da Rosa; Patricia Viana da Rosa (Taylor & Francis Group, 2022)
Purpose This study aims to correlate female sexual dysfunctions and dissatisfaction with female university students' body image. Methods 276 female university students completed an online questionnaire, including sociodemographic data, the Female Sexual Function Index, and the Body Shape Questionnaire. Results 31.1% reported some degree of dissatisfaction with body image, and 39.5% had a risk of female sexual dysfunction. The majority of women with a risk of female sexual dysfunctions (69.4%) had no concerns with shape, and the majority of women without sexual problems (67.7%) had no concerns with shape. Pearson's coefficient underlined no correlation between Body Shape Questionnaire and Female Sexual Function Index domains. Conclusion The body image perception did not seem to affect the sexual function of female university students in our sample. However, it is important to further investigate these variables to improve women's quality of life.